Functional effects of cannabinoids during dopaminergic specification of human neural precursors derived from induced pluripotent stem cells. (30th March 2016) - Stanslowsky, Nancy; Jahn, Kirsten; Venneri, Anna; Naujock, Maximilian; Haase, Alexandra; Martin, Ulrich; Frieling, Helge; Wegner, Florian
Abstract: Among adolescents cannabis is one of the most widely used illicit drugs. In adolescence brain development continues, characterized by neuronal maturation and synaptic plasticity. The endocannabinoid system plays an important role during brain development by modulating neuronal function and neurogenesis. Changes in endocannabinoid signaling by Δ 9 ‐tetrahydrocannabinol (THC), the psychoactive component of cannabis, might therefore lead to neurobiological changes influencing brain function and behavior. We investigated the functional maturation and dopaminergic specification of human cord blood‐derived induced pluripotent stem cell (hCBiPSC)‐derived small molecule neural precursor cells (smNPCs) after cultivation with the endogenous cannabinoid anandamide (AEA) and the exogenous THC, both potent agonists at the cannabinoid 1 receptor (CB1 R). Higher dosages of 10‐μM AEA or THC significantly decreased functionality of neurons, indicated by reduced ion currents and synaptic activity. A lower concentration of 1‐μM THC had no marked effect on neuronal and dopaminergic maturation, while 1‐μM AEA significantly enhanced the frequency of synaptic activity. As there were no significant effects on DNA methylation in promotor regions of genes important for neuronal function, these cannabinoid actions seem to be mediated by another than this epigenetic mechanism. Our data suggest that there are concentration‐dependent actions of cannabinoids on neuronal function in vitro indicating neurotoxic, dysfunctional effects of 10‐μM AEA and THC during human neurogenesis. Abstract : High dosages of the endocannabinoid anandamide (AEA) or Δ 9 ‐tetrahydrocannabinol (THC), the psychoactive component of cannabis, significantly reduced synaptic activity of neurons differentiated from human induced pluripotent stem cells. Lower concentrations of THC had no marked effect, while low AEA doses even enhanced the frequency of synaptic currents. Changes in endocannabinoid signalling might therefore lead to neurobiological changes influencing brain development, function and behaviour.